Control limitations of a cascaded H-bridge converter in solid-state substation applications - Amara, Fatima (2024)
A substantial transition is underway in the present era, characterised by a growing adoption of electric vehicles (EVs) and the integration of additional renewable energy sources into the utility grid. This shift is necessary for mitigating greenhouse gas emissions and addressing the increasing energy demand. Power electronics is a key facilitator in this transformation, mainly as the integration of small-scale renewable energy sources and EVs occurs at a low voltage DC level (LV) while the existing grid utility operates on an AC system. Consequently, there is an escalating demand for connecting various components to either low DC or AC voltage. An actual example of this integration is evident in the UNFLEX project, where diverse loads with varying voltage ratings are connected to each port, functioning as a power electronics-based transformer. This study concentrates explicitly on a single port of the UNIFLEX-PM converter linked to a low-voltage grid, where multilevel converters such as cascaded H-bridge converters are chosen.